Simulasi Kinerja Modulasi Pada Jaringan WiMAX Dengan Menggunakan Simulator OPNET Modeller 14.0 - Ilham Dwi Anshori; Anhar Anhar; Yusnita Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Access communication fast, flexible and reliable is needed to support the growing information technology. Therefore, needed a network that can meet those criterias, one of which is WiMAX (Worldwide Interoperability for Microwave Access). One of features that is given to optimize the quality of the WiMAX network is to use a modulation technique, such as QPSK, 16QAM, and 64QAM. The purpose of this study is to analyze the performance of WiMAX networks that include Bit Error Rate (BER), Signal to Noise Ratio (SNR), delay and throughput. In this research, the WiMAX network is simulated using OPNET simulator which consists of two scenarios. In Scenario 1 consists of 3 cell with 9 users, while the second scenario consists of 4 cell with 12 users. Research shows that the lowest BER value in scenarios 1 and 2 is achieved with QPSK modulation with a value of 8 x 10-6 and 8,05 x 10-6. While the highest SNR value in scenario 1 and 2 is achieved with QPSK modulation with a value of 34.25 dB and 44.06 dB. The calculation of throughput, highest throughput inscenarios 1 and 2 is achieved with 64QAM modulation with a value of 60.79 Mbps and 52.60 Mbps. As for the delay calculation, the value of the lowest delay in scenarios 1 and 2 isachieved with QPSK modulation with a value of 7.16 ms and 4.20 ms.Keywords : modulation techniques , BER, SNR, delay, throughput